2016
DOI: 10.2134/ael2015.10.0006
|View full text |Cite
|
Sign up to set email alerts
|

Increased Temperatures Have Dramatic Effects on Growth and Grain Yield of Three Maize Hybrids

Abstract: C limate change impacts on agricultural productivity are linked to the positive effects of increasing carbon dioxide (CO 2 ), negative effects of increasing temperatures, and variable effects of precipitation timing and amounts. Projections of crop productivity under scenarios of climate change have ranged from less than 5% with temperature increases of less than 1°C (Hatfield et al., 2011) to a decrease of more than 50% in maize (Zea mays L.) and soybean [Glycine max (L.) Merr.] (Schlenker and Roberts, 2009).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 14 publications
(21 reference statements)
6
44
0
2
Order By: Relevance
“…There is a differential response of plants to temperature throughout the growth cycle, and the recent results by Laza et al (2015) for rice showed that high night temperatures had no effect during the vegetative stage; however, high nighttime temperatures during the reproductive stage reduced yields because of the increased dark respiration rate and spikelet degeneration. This is similar to the results of Hatfield and Prueger (2015) and Hatfield (2016) from their controlled environment studies with high nighttime temperatures (plus 3C above normal temperatures) on maize yield which showed reductions of over 50% in maize grain yield.…”
Section: Crop Progress and Productivitysupporting
confidence: 87%
See 1 more Smart Citation
“…There is a differential response of plants to temperature throughout the growth cycle, and the recent results by Laza et al (2015) for rice showed that high night temperatures had no effect during the vegetative stage; however, high nighttime temperatures during the reproductive stage reduced yields because of the increased dark respiration rate and spikelet degeneration. This is similar to the results of Hatfield and Prueger (2015) and Hatfield (2016) from their controlled environment studies with high nighttime temperatures (plus 3C above normal temperatures) on maize yield which showed reductions of over 50% in maize grain yield.…”
Section: Crop Progress and Productivitysupporting
confidence: 87%
“…The effect of increasing CO 2 on plant productivity is generally positive with enhanced production and improved water use efficiency . Projections of temperature increase showed a large range in crop productivity with estimates of around 5% with temperature increases of 1°C (Schlenker and Roberts 2009;Hatfield et al 2011) to over 50% in maize and soybean under extreme warming (Schlenker and Roberts 2009;Hatfield 2016). Rising temperatures increase the rate of phenological development and reduced productivity because of the shortened growth cycle .…”
Section: Crop Progress and Productivitymentioning
confidence: 99%
“…When subjected to a 4 °C temperature increase in chamber studies, maize grain yield was found to decrease by 84-100% while vegetative biomass was less affected (Hatfield, 2016). Less severe reductions in maize grain yield have been documented in field studies (Ruiz-Vera et al, 2015).…”
Section: Resultsmentioning
confidence: 95%
“…The response of maize growth to elevated temperature has been studied in the literature ( -Vera et al, 2015;Hatfield, 2016). When subjected to a 4 °C temperature increase in chamber studies, maize grain yield was found to decrease by 84-100% while vegetative biomass was less affected (Hatfield, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation